ANALYSIS OF THE CONTRIBUTION OF KUTAI KARTANEGARA REGENCY IN MEETING FOOD NEEDS OF EAST KALIMANTAN PROVINCE BASED ON SUPERIOR FOOD COMMODITIES IN THE AGRICULTURAL SECTOR - Mutiara Kartika Dewi; Jiuhardi Jiuhardi; Irsan Tricahyadinata (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
The aims of this study are (1) to determine the contribution of the leading agricultural sector of Kutai Kartanegara Regency to the fulfillment of food needs in East Kalimantan Province. (2) Knowing the agricultural sub-sector and commodities that are the mainstay in Kutai Kartanegara Regency. This research is a quantitative descriptive research. The data used in this study are secondary time series data from 2016 to 2020 sourced from BPS and the Agriculture and Livestock Service Office of Kutai Kartanegara Regency. The analytical method used is contribution analysis, shift share and Location Quotient (LQ). The results showed that in 2016-2020 the contribution of the agricultural sector of Kutai Kartanegara Regency to the fulfillment of the food needs of East Kalimantan Province was 38.82%. From the shift share analysis, it is known that the growth rate of the agricultural sector has a positive value of 0.2. This is also reflected in the value of the differential shift (Cij). Cij agricultural sector has a positive value of 538.79 billion which shows that the agricultural sector has a competitive value. The growth rate (Dij) of Kutai Kartanegara Regency is 2209.47 billion.The leading sub-sectors are fisheries sub-sector, food crops sub-sector, and horticulture sub-sector. Aquaculture commodities are the flagship of the fisheries sub-sector. Rice is the leading commodity in the food crop sub-sector. Meanwhile, ginger and temu lawak are the leading commodities in the horticulture sub-sector.